Identification of RNA silencing suppressor encoded by citrus chlorotic dwarf-associated virus - Ye, Xiao; Ding, Dongdong; Chen, Yuan; Liu, Chuang; Li, Zhongan; Lou, Binghai; Zhou, Yan (Frontiers in Microbiology, 2024)
Introduction Citrus chlorotic dwarf-associated virus (CCDaV) is an economically important citrus virus associated with leaf curling, deformation, and chlorosis found in China. Plants have evolved RNA silencing to defend against viral infections; however, the mechanism by which CCDaV suppresses RNA silencing in citrus remains unknown. Methods Six proteins encoded by CCDaV were ectopically expressed in Nicotiana benthamiana 16c using the pCHF3 vector to identify RNA-silencing suppression activities. Results V2 protein encoded by CCDaV suppressed local RNA silencing and systemic RNA silencing triggered by GFP RNA, but did not impede short-distance movement of the RNA silencing signal in N. benthamiana 16c. GFP fluorescence observations showed that the ability of V2 protein to suppress RNA silencing was weaker than tomato bushy stunt virus P19. Deletion analysis showed that the putative nuclear localization signal (NLS, 25–54 aa) was involved in the RNA silencing suppression activity of V2 protein. Furthermore, V2 protein cannot block dsRNA-triggered RNA silencing. The subcellular localization assay suggested that V2 protein was localized to nucleus of N. benthamiana. Conclusion Overall, the results of this study demonstrate that CCDaV-V2 acts as an activity of silencing suppression. This is the first reported RNA-silencing suppressor encoded by Citlodavirus and will be valuable in revealing the molecular mechanism of CCDaV infection.